Electro-Optic Sampling with Percent-Level Detection Efficiency - Hofer, Christina; Gerz, Daniel; Gebhardt, Martin; Heuermann, Tobias; Butler, Thomas P.; Gaida, Christian; Limpert, Jens; Krausz, Ferenc; Pupeza, Ioachim (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Electro-optic sampling (EOS) [1] is widely used for broadband and sensitive characterization of mid-infrared (MIR) waveforms and spectroscopy [2] , [3]. GaSe as the nonlinear crystal and 10-fs gate pulses at 100-mW average power, generated in highly nonlinear fibres from Er-doped fibre lasers, are commonly employed for broadband sampling of MIR fields [4]. Using Yb-based laser systems to generate high-power, 1030-nm gate pulses allowed us to push the detection efficiency to a record-level of 0.5 %, limited by the damage threshold of GaSe [2]. However, the short gate pulse wavelength strongly limits the phase matching bandwidth [5].
CRIS-Team Scopus Importer:2023-04-20